INKA, an integrative data analysis pipeline for phosphoproteomic inference of active kinases. Issue 5 (24th May 2019) - Beekhof, Robin; van Alphen, Carolien; Henneman, Alex A; Knol, Jaco C; Pham, Thang V; Rolfs, Frank; Labots, Mariette; Henneberry, Evan; Le Large, Tessa YS; de Haas, Richard R; Piersma, Sander R; Vurchio, Valentina; et al.
Abstract :